EP772 Testing for concordance of somatic and germline BRCA1/2 pathogenic mutations in ovarian cancer patients eligible for PARP inhibitors therapy: large single-site institution experience. (1st November 2019) - Akaev, I; Chau, C; Uherek, M; Rahimi, S; Gardner, F; Yeoh, CC
Abstract : Introduction/Background: Incidence of Ovarian Cancer (OC) in Portsmouth is approximately 110 cases per year, standing as the 10th largest city in the UK. Individuals with germline BRCA1/2 (gBRCA1/2) alterations treated with the PARP inhibitors (PARPi) tend to respond better than patients with wild-type BRCA1/2. Additionally, somatic BRCA1/2 (sBRCA1/2) alterations induce the sensitivity to PARPi. The aim of the study was to investigate the rate of concordance of gBRCA1/2 with sBRCA1/2 pathogenic mutations to increase screening uptake for prescription of the newly NICE approved PARPi tablets available for gBRCA and sBRCA mutation carriers. Methodology: 70 patients diagnosed with ovarian cancer were screened: 50 with High Grade Serous Carcinoma (HGSC), 2 Low Grade Serous Carcinoma (LGSC), 4 Clear Cell Carcinoma (CCC), 2 Carcinosarcoma, 11 Endometrioid Adenocarcinoma (EdAd) and 1 mucinous carcinoma. Patients were tested for BCRA1/2 germline mutations upfront, followed by testing of tumour specimens for somatic mutations using NGS. Results: 9 cases had gBRCA1/2 pathogenic mutations: 5 HGSC had gBRCA1, 3 HGSC and 1 EdAd had gBRCA2. 7 cases had sBRCA1/2 mutations: 4 gBRCA1 and 3 gBRCA2 HGSC had sBRCA1 and sBRCA2 respectively. EdAd gBRCA2 had no somatic mutations; 1 HGSC patient with gBRCA1 had no sBRCA1/2 mutations. 1 HGSC wild-type gBRCA showed pathogenic sBRCA1 frameshift mutation. 2 EdAd and 1 CCC wild-type gBRCA showed sBRCA1/2 mutations of unknown clinical significance. LGSC, carcinosaromas and mucinous carcinoma were wild-type gBRCA with no somatic mutations detected. Conclusion: Detection of both germline and somatic BRCA1/2 mutations is required for effective PARPi treatment. Somatic tests should be offered to increase the number of patients suitable for targeted therapy. The consistency of gBRCA1/2 uptake (13%) was in keeping with published data, whereas the sBRCA1/2 uptake was 11.4%, which is less than the expected 15%. More research into cases with sBRCA1/2 mutations of unknown clinical significance is warranted. Disclosure: Nothing to disclose.